Pengaruh Model Pembelajaran Cooperative Learning Bernuansa Lingkungan Berbantuan Media Audiovisual Terhadap Hasil Belajar IPS Ditinjau dari Minat Outdoor Siswa Kelas IV SDN Gugus 2 Selong Lombok Timur Tahun Pelajaran 2019/2020 - Made Ayu Pransisca (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study was aim to investigate the effect of cooperative learning model with environmental nuances assisted by audiovisual media towards students’ social learning outcomes reviewed from students’ outdoor interest on grade IV SDN Gugus 2 Selong, East Lombok. This study used quasi-experimental approach with post test two group factorial design. The population of the study were 143 students. The sample of this study was 76 students taken by random sampling technique. Student outdoor interest data were taken by questionnaire. Meanwhile, students’ learning outcomes data were collected by tests. The Data of this study were analyzed using Anava AB assisted by SPSS 16.00 for windows. The results showed that: 1) There was a significant difference of students’ social learning outcomes between students cooperative learning model with environmental nuances assisted by audiovisual media and students conventional learning (FA count = 14.489, with p <0.05), 2) There was a significant interaction effect between the cooperative learning model with environmental nuances assisted by audiovisual media and outdoor interest towards students’ social learning outcomes (FA count = 36.202, with p <0.05), 3) For students high outdoor interest, There was difference students’ social learning outcomes between students Cooperative Learning model with environmental nuances assisted by audiovisual media and students conventional learning (tcount> ttable = 6.934> 1,980), 4) For students low outdoor interest, there was no significant difference of students’ social learning outcomes between students Cooperative Learning model with environmental nuances assisted by audiovisual media and students conventional learning (tcount <ttabel = 1.561 <1,980).